Consumer theory with misperceived tastes - Geoffroy De Clippel; Kareen Rozen (Brown University, Department of Economics, 2018)
Incorporating bounded rationality into the classic consumer theory setting, we study the testable implications of a consumer who may have trouble consistently assessing her subjective tastes. Our model of E-Rationalizability, which bounds the consumer's misperception of her marginal rates of substitution, may arise from various choice heuristics. It also offers a natural, preference-based measure of departure from rationality that is more demanding than Afriat's measure.
Keywords: 330